Stimulation of arbuscular mycorrhizal fungi symbiosis with soursop (Annona muricata L.) using rice husk bochar - Harun, Nur Saidahtul Nadiah (2019)
Soursop (Annona muricata L.) known for its medicinal and health benefits has been increasingly planted in Malaysia. However, there are limited information on soursop cultivation under Malaysian highly weathered soils. Cultivation of soursop can be further explored with incorporation of beneficial microorganism namely arbuscular mycorrhizal fungi (AMF) and organic matter such as rice husk biochar (RHB) as tools in soil management. Thus, local evaluation of AMF sources and RHB application rate on soursop seedlings under Malaysian soil is crucial to fill the knowledge gap. This study seek to stimulate arbuscular mycorrhizal fungi (AMF) symbiosis with soursop (Annona muricata L.) using rice husk biochar (RHB) while observing the RHB and AMF effects on soursop seedlings growth, soil physico-chemical as well as biological properties. This was done by growing 2 months old soursop seedlings in 2 separate glasshouse experiments. In the first experiment, 2 factors which are 4 RHB rates (0, 10, 15 and 20 t/ha RHB) with and without AMF inoculation were tested on soursop seedlings for 4 months. The study was arranged in Randomized Complete Block Design (RCBD) and with 4 replications. After 4 months of transplanting, soil treated with RHB and AMF significantly improved mycorrhizal colonisation and sporulation, soursop (Annona muricata) plant growth and plant nutrient uptake. Lower rate of RHB with AMF (+AMF + 10 t/ha RHB) promoted plant growth and gave similar effects to that at higher RHB rate (15 t/ha and 20 t/ha RHB) in stimulating AMF development. Soils treated with 10 t/ha RHB either with or without AMF, improved 4.33 % AMF sporulation, 9.30 % plant growth, 2.2 % root development, and 2.57 % plant P uptake compared to control While the first experiment suggested that AMF species inoculated in this study (Glomus mosseae) was able to form symbiotic association with soursop at lower application rate (<10 t/ha RHB), further determination on the AMF species compatibility, suitability and host performance at similar RHB rate. Thus, various AMF sources (AMFS 1, AMFS 2 and AMFS 3) in combination were carried out with or without 10 t/ha RHB were evaluated on soursop seedlings under glasshouse conditions. After 2 months of transplanting, all mycorhizal sources either individually (single species) or combination (mixed species) significantly increased AMF sporulation (31%) and improved growth of soursop seedlings compared to non-inoculated control. Mixed AMF species found in AMFS 2 was able to stimulate AMF and plant growth (15.5 % plant height, 0.32 % chlorophyll content as well as bacterial population (0.02%). In conclusion, RHB at lower rate (10 t/ha RHB) was optimal and did not have any detrimental effects to AMF or soursop seedlings. While locally isolated Glomus moassae (single species) and commercial inoculums were able to form symbiotic relationship with soursop roots, having more than one AMF species would result in better soursop growth. Inoculating soursop seedlings with AMF at nursery stage up to 6 months old may provide more chances for the plant to establish symbiotic relationship with AMF before transplanted to field.